menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve: 6^2x - 3 = 6^-2x+1 O x=-1 x=0 O x=1 0 x=4
asked
May 16, 2021
188k
views
0
votes
Solve: 6^2x - 3 = 6^-2x+1
O x=-1
x=0
O x=1
0 x=4
Mathematics
college
Stormfield
asked
by
Stormfield
4.8k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
2
votes
Answer:
C
Explanation:
Bitpshr
answered
May 16, 2021
by
Bitpshr
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
3
votes
Answer:
6^2x-3=6^-2x+1 =>X=4
Jaredwoodard
answered
May 20, 2021
by
Jaredwoodard
4.8k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.2m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
I need to simplify this expression.
Need answer to math problem!!!
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org